The queer time of death: Temporality, geopolitics, and refugee rights. (December 2014) - Shakhsari, Sima
Using the ethnographic data from interviews with the Iranian queer and transgender refugee applicants in Turkey, the UNHCR, and NGOs in Istanbul, Ankara, Denizli, Kayseri, and Nevsehir, I explore the way that refugee rights as a temporally and spatially contingent concept normalizes queer and transgender refugee subjects, while managing the lives and deaths of different populations. Through examining the chronopolitics and geopolitics of rights within the refugee discourse, I point to inconsistencies in the universality of human rights and argue that while the designation of an act as "violation of human rights" committed by states or citizens, is arbitrary and contingent on the place and time of the act, the recognition of the refugee in the human rights regimes relies on essentialist and timeless notions of identity that travel in the teleological time of progress. The Iranian queer and trans refugees in Turkey are suspended in an in-between zone of recognition where rightfulness and rightlessness come together in a temporal standstill. The "protection" of trans and queer refugees under the rhetoric of rights in this in-between zone is tied to the management of life and death of populations through the politics of rightful killing.